2019
DOI: 10.1101/gr.243030.118
|View full text |Cite
|
Sign up to set email alerts
|

Systems genetics of the Drosophila metabolome

Abstract: How effects of DNA sequence variants are transmitted through intermediate endophenotypes to modulate organismal traits remains a central question in quantitative genetics. This problem can be addressed through a systems approach in a population in which genetic polymorphisms, gene expression traits, metabolites, and complex phenotypes can be evaluated on the same genotypes. Here, we focused on the metabolome, which represents the most proximal link between genetic variation and organismal phenotype, and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…2), displaying same level of genetically determined variability as the Drosophila transcriptome. 30 It has previously been shown that metabolome variation appears to have a genetic signature, 18 but also that the metabolome is highly variable among sexes 18,49 and change with age. [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2), displaying same level of genetically determined variability as the Drosophila transcriptome. 30 It has previously been shown that metabolome variation appears to have a genetic signature, 18 but also that the metabolome is highly variable among sexes 18,49 and change with age. [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] The metabolome is closer to the functional phenotype than transcriptomics and proteomics and recent study based on investigating 453 metabolites in 40 DGRP lines suggest that the metabolome might constitute a reliable predictor of organismal phenotypes and that the metabolome provide novel insights into the underpinnings of complex traits and its genetic basis. 18 Here we elaborate on the findings by Zhou et al melanogaster. 23,24 NMR metabolomics constitute a highly reproducible technique that in contrast to mass spectrometry allows for metabolic profiling of the total complement of metabolites in a sample.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…eQTLs with both cis-and trans-effects can be assembled into directed transcriptional networks of regulator and target genes (Liu et al 2008;Bryois et al 2014;Fagny et al 2017). Elucidating such regulatory transcriptional networks will facilitate understanding how the effects of individual variants propagate through the network and how multiple variants together regulate gene expression and affect complex traits (Liu et al 2008;Nicolae et al 2010;Bryois et al 2014;Fagny et al 2017) and will improve genomic prediction (Zhou et al 2020).…”
mentioning
confidence: 99%
“…Combining eQTL studies with GWAS revealed that significant hits for many diseases are likely to be eQTLs, meaning that disease-associated SNPs presumably act by altering gene expression levels ( Nicolae et al 2010 ). As other types of omic data became available, studies mapping protein QTL (pQTL) ( Chick et al 2016 ) and metabolic QTL (mQTL) ( Kraus et al 2015 ; Zhou et al 2020 ) have helped elucidate how the effect of genetic variation percolates through intermediate molecular layers before affecting phenotypes.…”
mentioning
confidence: 99%